2003
DOI: 10.1128/aac.47.12.3859-3866.2003
|View full text |Cite
|
Sign up to set email alerts
|

Triclosan as a Systemic Antibacterial Agent in a MouseModel of Acute BacterialChallenge

Abstract: The upsurge of multiple-drug-resistant microbes warrants the development and/or use of effective antibiotics. Triclosan, though used in cosmetic and dermatological preparations for several decades, has not been used as a systemic antibacterial agent due to problems of drug administration. Here we report the striking efficacy of triclosan in a mouse model of acute systemic bacterial infection. Triclosan not only significantly extends the survival time of the infected mice, it also restores blood parameters and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
23
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 38 publications
2
23
0
Order By: Relevance
“…In the past, triclosan has already been in use as antibacterial agent. Based on previous reports (6,20) and our current data, it is clear that triclosan is active against both liver-stage and blood-stage parasites. Different kinds of molecules are known to target PfENR (35-37) and close to a hundred derivatives of triclosan have recently been examined for the blood-stage parasite enzyme.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…In the past, triclosan has already been in use as antibacterial agent. Based on previous reports (6,20) and our current data, it is clear that triclosan is active against both liver-stage and blood-stage parasites. Different kinds of molecules are known to target PfENR (35-37) and close to a hundred derivatives of triclosan have recently been examined for the blood-stage parasite enzyme.…”
Section: Discussionsupporting
confidence: 78%
“…Extensive studies have been performed on P. falciparum ENR (PfENR), using biochemical (14-17) as well as structural (12,18,19) tools, to understand the mechanism of PfENR inhibition by triclosan. Several studies have shown that triclosan is effective in killing the malaria parasites (blood stage) both in vitro and in vivo as well as in clearing an acute bacterial infection (6,12,20).…”
Section: Introductionmentioning
confidence: 99%
“…It inhibits recombinant PfFabI with an IC 50 of 70 nM and arrests the growth of P. falciparum in red blood cell cultures with an IC 50 of 0.7 M (12, 34). Its potency as a systemic antibacterial agent has also been explored (28). For studying the inhibition by triclosan, all of the FAS enzymes were added sequentially, in contrast to previous reaction setups in which all of the FAS enzymes were added together in the reaction mixture.…”
Section: Resultsmentioning
confidence: 99%
“…However, the increase in azole use has precipitated a rise in drug resistance in clinical isolates. Triclosan, a chlorinated aromatic compound, has antimicrobial (4,8,20), antiparasitic (26), and anti-inflammatory (1,24) activities. It has been used in personal care products (2).…”
mentioning
confidence: 99%
“…An agar diffusion test can provide more visually convincing results. A combination treatment with triclosan has been previously demonstrated to significantly enhance the efficacy of triclosan against microbes (20,22). In contrast to various previous reports (20,22), triclosan is a better synergist to fluconazole against C. albicans.…”
mentioning
confidence: 99%